Building the Next Generation of Humanized Hemato-Lymphoid System Mice - Martinov, Tijana; McKenna, Kelly M.; Tan, Wei Hong; Collins, Emily J.; Kehret, Allie R.; Linton, Jonathan D.; Olsen, Tayla M.; Shobaki, Nour; Rongvaux, Anthony (Frontiers in Immunology, 2021)
Since the late 1980s, mice have been repopulated with human hematopoietic cells to study the fundamental biology of human hematopoiesis and immunity, as well as a broad range of human diseases in vivo. Multiple mouse recipient strains have been developed and protocols optimized to efficiently generate these “humanized” mice. Here, we review three guiding principles that have been applied to the development of the currently available models: (1) establishing tolerance of the mouse host for the human graft; (2) opening hematopoietic niches so that they can be occupied by human cells; and (3) providing necessary support for human hematopoiesis. We then discuss four remaining challenges: (1) human hematopoietic lineages that poorly develop in mice; (2) limited antigen-specific adaptive immunity; (3) absent tolerance of the human immune system for its mouse host; and (4) sub-functional interactions between human immune effectors and target mouse tissues. While major advances are still needed, the current models can already be used to answer specific, clinically-relevant questions and hopefully inform the development of new, life-saving therapies.